COST AND RETURN ANALYSIS OF IRRIGATED UPLAND TOMATO (Lycopersicon Esculentum) PRODUCTION IN GOMBE STATE, NIGERIA - Makka, T. B.; Murtala, N.; Idi, S.; Haruna, U. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the cost and return analysis of irrigated upland tomato (Lycopersicon Esculentum) production, in Gombe State, Nigeria. Multi-stage random sampling procedure was used to select 459 respondents. Data were collected using structured questionnaire and were analysed using descriptive and inferential statistics. The result revealed that Most of the types of farms implements use for dry season tomato production in the study areas were tractors (32.4%), hand tools (37.6%) and animal traction (30.0%). Capital for dry season tomato production, the respondents in Dukku, Nafada, funakaye and Yamaltu Deba LGA respondents had a mean capital of N212,747.36, N183,662.55, N261,540.30, and N204,785.956 respectively. The findings also revealed the result of maximum likelihood estimate of parameters of the stochastic frontier production function of dry season tomato farming in the study area reveal that farm size (P< 0.001), labour (P< 0.001), farming experience (P< 0.001), and capital (P< 0.001) were the major factors statistically affecting the respondents rice production at 1%. The analysis of dry season maximum likelihood estimate of the parameter of stochastic frontier cost of tomato production showed that ploughing (P< 0.001), transplanting (P< 0.001), harvesting (P< 0.001) and capital (P< 0.001) were the determinant of cost of output of the respondents. The result further reveals the costs and return of dry season tomato farming in the study area depicts that the total variable cost of production was ₦2,384,894 with a total cost of production which is the total variable plus the fixed cost of ₦3,266,031. The revenue realized was ₦4,070,558. The net farm income for the dry season tomato farmers for one hectare in the study area was ₦804,529.23. The profit index of the respondents was ₦1.7. The major constraints to the irrigated upland tomato production were inadequate water for irrigation (23.0%), lack of irrigation facilities (20.7%), heat stress and drought (27.2%) preventing maximum productions in the study area. In addition, constraints to irrigated upland tomato farming in the study area includes high cost of irrigation services (26.0%), high-cost fertilizer (19.3%), high cost of pesticide (20.9%) and high cost of insecticide (18.2%). It was concluded that the respondents are operating at a lost and again the labour cost looking at the high cost incurred from production which clearly shows that there was over utilization of resources especially in the area of labour cost. The study made the following recommendations; efforts should be made to improve access to adequate water for irrigation purposes, there is a need to provide modern irrigation facilities to farmers to improve water management and efficiency, there is a need to promote value addition in tomato farming through processing and packaging to increase the shelf life of tomatoes and reduce post-harvest losses and farmers should be encouraged to formed cooperatives to be united in one voice to have a bargaining power over labour cost and can also make request to government on their needs and access inputs and training from policy support programme to achieve optimal yield.